2021
DOI: 10.5194/acp-2020-1258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Gas-Particle Partitioning Coefficients of Atmospheric Molecules with Machine Learning

Abstract: Abstract. The formation, properties and lifetime of secondary organic aerosols in the atmosphere are largely determined by gas-particle partitioning coefficients of the participating organic vapours. Since these coefficients are often difficult to measure and to compute, we developed a machine learning model to predict them given molecular structure as input. Our data-driven approach is based on the dataset by Wang et al. (Atmos. Chem. Phys., 17, 7529 (2017)), who computed the partitioning coefficients and sat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Prisle et al found the same as expressed by a very low experimentally derived hydrophilicity factor for α-pinene + O 3 SOA at high RH. 60 Recently, Lumiaro et al 72 used a machine learning-based method to predict COSMOtherm estimated saturation vapor pressures and gas-to-particle partitioning coefficients. Such methods may be used to replace computationally heavy COSMOtherm calculations in the future.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prisle et al found the same as expressed by a very low experimentally derived hydrophilicity factor for α-pinene + O 3 SOA at high RH. 60 Recently, Lumiaro et al 72 used a machine learning-based method to predict COSMOtherm estimated saturation vapor pressures and gas-to-particle partitioning coefficients. Such methods may be used to replace computationally heavy COSMOtherm calculations in the future.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
“…Recently, Lumiaro et al used a machine learning-based method to predict COSMO therm estimated saturation vapor pressures and gas-to-particle partitioning coefficients. Such methods may be used to replace computationally heavy COSMO therm calculations in the future.…”
Section: Discussionmentioning
confidence: 99%